CHILD PARENTING IN EARLY MARRIAGE COUPLES IN FLAT VILLAGE DAYEUHLUHUR DISTRICT CILACAP REGENCY (BELIA: Early Childhood Education Papers, 2022)
This study focused on childcare in early marriage couples in Datar Village, Dayeuhluhur District, Cilacap Regency. The purpose of this study is to describe childcare in early marriage couples in Datar Village, Dayeuhluhur District, Cilacap Regency. In addition, the study also aims to explain the inhibitory factors that arise in childcare in early marriage couples. This type of research is qualitative descriptive. The subjects in this study involved 3 (three) main respondents, namely women who married early and involved 5 (five) supporting respondents consisting of three neighbors of the main respondents, the village head and one KUA (Office of Religious Affairs) officials. Data collection techniques use interviews, observations and documentation. Based on interviews, customary and educational factors are considered to be the most dominant factors to cause early marriage in Dayeuhluhur District. The customary factor where children who go to junior high school begins to be matched and this becomes cultured in the area, for educational factors where the children there are mostly junior high school graduates and the highly educated are slightly because the distance from the village to high school is quite far away. Data analysis uses Miles and Huberman's theory of data reduction, data presentation and inference. Then the validity of the data is viewed using data triangulation. The results showed that 1) Pola fostering children of early marriage couples in Datar Village, Dayehluhur District, Cilacap Regency is a democratic parenting while still providing advice to children and implementing a reward and punishment system so that children can behave disciplined and responsible with their actions. 2) In terms of obstacles there are two, namely internal and external obstacles. Internal barriers come from within the parents themselves while external barriers come from the environment, culture and socio-economic status of parents who perform early marriage in Datar Village. Keywords : childcare; early marriage.